A laser-based synthesis route for magnetic metallic glass nanoparticles. (October 2021) - Liang, Shun-Xing; Salamon, Soma; Zerebecki, Swen; Zhang, Lai-Chang; Jia, Zhe; Wende, Heiko; Reichenberger, Sven; Barcikowski, Stephan
Abstract: Phase control, especially for amorphous phase, is challenging with pulsed laser ablation in liquid (LAL), where ablated materials experience crystallization even at extreme cooling rate during particle solidification processes. Here, metallic glass nanoparticles (MG-NPs) were prepared by picosecond-laser ablation of a Fe78 Si9 B13 metallic glass (MG) in several organic solvents (i.e. ethanol, acetone, acetonitrile). The employment of ternary MG precursor effectively avoids elemental segregation of plasma-induced matters; meanwhile, in-situ carbonization by decomposition of solvents further complexes the alloy system to successfully achieve amorphous phase in the NPs. The carbon-rich molecules in solvents enhance the relative fraction of MG-NPs, while parasitic Fe oxide phases are formed due to the competition kinetics of oxygen (e.g. dissolved oxygen and miscible water). Further magnetic measurements and Mössbauer spectra confirm the contribution of MG and Fe oxide NPs to the magnetism. This work provides a new route to produce magnetic MG-NPs for further multifunctional applications. Graphical abstract: Image, graphical abstract